‘Education is the only Choli-Bangadi I am Giving to my Daughters’ - Suradkar, Sindhu (Prabuddha: Journal of Social Equality; Vol 5 No 1 (2020): Political Geographies, 2021)
Intergenerational conversations in emancipatory movements empower each new generation with the pedagogy about who we are. Both the unchanging and changing aspects of the social structures are transmitted through these conversations. Sindhu Suradkar has been a community worker from the time she completed her studies, here, she is in conversation with Pradnya Garud. The memories of her natal and marital families, and their role in shaping her values and social commitments forms a large part of this exchange.